Abundance of small cetaceans in waters of the central Spanish Mediterranean - Gómez de Segura, Amaia (2006)
Seasonal aerial surveys were conducted in the waters of the central Spanish Mediterranean from 2001 to 2003 using line transect sampling methodology to estimate cetacean abundance. The density of the three most abundant species, striped dolphin (Stenella coeruleoalba), bottlenose dolphin (Tursiops truncatus) and Risso’s dolphins (Grampus griseus) was estimated. In the case of the first two species, density was estimated accounting for the proportion of submerged animals, while for Risso’s dolphin only the surface density could be estimated. The striped dolphin was the most abundant species in the study area with a mean density of 0.489 dolphins km-2 (95% CI = 0.339 - 0.705) and a mean abundance of 15,778 dolphins (95% CI = 10,940 - 22,756). This density is comparable to that obtained in the International Ligurian Sea Cetacean Sanctuary. Striped dolphins were observed throughout the whole year and no seasonal changes in density were detected. The mean density of bottlenose dolphins was an order of magnitude lower than that of striped dolphin (0.041 dolphins km-2; 95% CI = 0.023 - 0.075) with a mean abundance of 1,333 dolphins (95% CI = 739 - 2,407). The Risso’s dolphin had a surface estimated density of 0.015 dolphins km-2 (95% CI = 0.005 - 0.046) and a mean abundance of 493 dolphins (95% CI = 162 - 1,498). These results provide valuable biological information useful to develop conservation plans and establish a baseline for future population trends studies.